The development impact of barter in developing countries : synthesis report - Outters-Jaeger, Ingelies; Organisation for Economic Co-operation and Development (Paris : Development Centre of the Organisation for Economic Co-operation and Development : [Washington, D.C. : sold by OECD Publications and Information Center], 1979)
The present study is the general summary report which concludes the research on the Development Impact of Barter in Developing Countries conducted by the Development Centre. Apart from a comparative analysis of the different case studies carried out in the project, it provides a theoretical discussion and general overview of the current role of barter-like trade in developing countries' foreign trade
Includes bibliographical references: p. 126-130.
osc 29/01/2019
Loans
Keywords: Barter; Developing countries